Study of a silica gel-water based dual mode adsorption chiller - Habib, K. (Engg Journals Publications, 2016)
This article presents analytical investigation results on the performance of dual-mode multi-bed adsorption cooling systems using silica gel-water pair. This novel adsorption chiller utilizes effectively low-temperature solar or waste heat sources of temperature between 40 and 85°C. Two operation modes are possible for the advanced chiller. The first operation mode will be to work as a highly efficient conventional chiller where the driving source temperature is between 60 and 85°C. The second operation mode will be to work as an advanced two-stage adsorption chiller where the available driving source temperature is very low (below 60°C). In the present work, a simulation study of a dualmode, four-bed silica gel-water adsorption chiller is undertaken. For a driving source temperature above 60°C, the chiller functions as a single stage four-bed adsorption chiller. However, the chiller works as a two stage four-bed adsorption chiller when the driving source temperature falls within the range from 40°C to 60°C. With a cooling water temperature of 30°C. It has been found that this dual mode adsorption chiller is capable to provide cooling throughout the year via measuring the coefficient of performance and the cooling capacity of the system.